A Comparative Survey of the Indradhvaja Ceremony (Gārgīyajyotiṣa 45) - Geslani, Marko (History of Science in South Asia)

(untitled) (University of Alberta Library, 2019)
This article gives a preliminary survey of Gārgīyajyotiṣa 45, a ritual description of the festival of Indra's Banner (indradhvaja), based on manuscript evidence. The testimony of Garga is compared to the description of the same rite in Varāhamihira's Bṛhatsaṃhitā (chapter 42), with reference to later Puranic versions. Since Varāhamihira has explicitly referenced Garga's text on multiple occasions, this comparison brings to light Varāhamihira's own innovations with respect to his source material. While Varāhamihira did not produce the ritual ex nihilo, he seems to have added greater specificity to the ritual's mantric content and overnight structure, and to the broader connectivity between the Indradhvaja festival and other events in the nascent royal calendar.